2021
DOI: 10.1080/16549716.2021.1892309
|View full text |Cite
|
Sign up to set email alerts
|

Making a COVID-19 vaccine that works for everyone: ensuring equity and inclusivity in clinical trials

Abstract: Coronavirus disease 2019 (COVID-19) mortality and morbidity have been shown to increase with deprivation and impact non-White ethnicities more severely. Despite the extra risk Black, Asian and Minority Ethnicity (BAME) groups face in the pandemic, our current medical research system seems to prioritise innovation aimed at people of European descent. We found significant difficulties in assessing baseline demographics in clinical trials for COVID-19 vaccines, displaying a lack of transparency in reporting. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The impact of COVID-19 in this population can be understood not only from a biological perspective but also regarding social or economic factors, with certain communities being more predisposed to suffering from poorer outcomes [ 74 ]. This is a critical issue to address, as a recent study found that only 25 out of 219 clinical trials have taken place in lower-middle or low-income countries, and up to 80% of the people recruited in active vaccination trials were not from ethnic minorities, leading to an underrepresentation of these populations [ 75 ]. Thus, it is imperative to also include these populations as a priority group for vaccination.…”
Section: Strategies and Considerations In Covid-19 Vaccination Programsmentioning
confidence: 99%
“…The impact of COVID-19 in this population can be understood not only from a biological perspective but also regarding social or economic factors, with certain communities being more predisposed to suffering from poorer outcomes [ 74 ]. This is a critical issue to address, as a recent study found that only 25 out of 219 clinical trials have taken place in lower-middle or low-income countries, and up to 80% of the people recruited in active vaccination trials were not from ethnic minorities, leading to an underrepresentation of these populations [ 75 ]. Thus, it is imperative to also include these populations as a priority group for vaccination.…”
Section: Strategies and Considerations In Covid-19 Vaccination Programsmentioning
confidence: 99%
“…As regards the principle of justice in connection with vaccinations, the first issue relates to equity in vaccine trial programs [ 20 , 21 ], and the second pertains to the agreements which make financing for research dependent on the supply of a certain number of vaccine doses [ 22 , 23 ]. The third issue concerns the distribution of the vaccines themselves.…”
Section: Covid-19 Pandemic and Equal Access To Treatment And Vaccinationmentioning
confidence: 99%
“…Therefore, the vaccination process cannot ignore the concept of equity as it is interpreted in the health domain. Research in PubMed with the query “(equity [Title]) AND (COVID-19)” showed that the problem of equity is strongly perceived from different points of view, starting from the ethics up to the social vision [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: The Digital Divide the Escape The Exposure Risk The Equitymentioning
confidence: 99%